Kesehatan Lingkungan Kerja Pendekatan Sosiologis - Risa Bernadip Umar; Muslimin B; Nursinah Nursinah; Nonis Nonis; Andri Wahyu Utomo; Titin Kuntum Mandalawati; Oktria Veni; Romi Mesra (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
The purpose of this study is to examine the function of Manado's Women's Empowerment and Child Protection Agency (P2TP2A) on Jl. City Hall No. 1 Tikala Ares, Tikala Subdistrict in dealing with incidents of domestic violence against women and children. The issue in this study is domestic violence against women and children. Methods of qualitative research. The goal of qualitative research methodologies is to produce a thorough, factual, and accurate portrayal. Observation, interviews, and documentation are all methods for gathering data. According to the findings of field study, there is a lot of domestic violence against women and children, and there is still violence that is carried out by using the hands with small strikes to blows that might make the victim's condition worse, way that it has an influence on the psychological and psychological development of children, and other elements. Economic considerations, early marriage, and intervention from others are all causes of violence